A política educacional do PT na Prefeitura Municipal de São Paulo (1989-1992): formulação e institucionalização - Paludeto, Melina Casari [UNESP]; Torres, Julio Cesar [UNESP] (My University, 2014)
It was investigated how the conceptions of PT for the educational area defended in national meetings of the party have configured as policies in the City Hall of São Paulo during 1989-1992. It was made an analysis of official documents and measures adopted by the Municipal Education Secretariat. Then, it could be concluded that the priorities of implementation of the PT proposal entitled popular public school were based on four categories: Democratization of Management; New Quality of Teaching; Movement of Adult and Youth Literacy (MOVA) and Democratization Access.

Investigou-se como as concepções do PT para a área educacional defendidas nos Encontros Nacionais do Partido configuraram-se enquanto políticas na Prefeitura Municipal de São Paulo no período 1989-1992. Foram analisados documentos e medidas adotadas pela Secretaria Municipal de Educação. Concluiu-se que as prioridades da implementação da proposta do PT intitulada escola pública popular foram sintetizadas em quatro eixos centrais: Democratização da Gestão; Nova Qualidade de Ensino; Movimento de Alfabetização de Jovens e Adultos (MOVA) e Democratização do Acesso.

Se investigó como las concepciones del PT para la área educacional defendidas en los Encuentros Nacionales del Partido se configuraron como políticas en el Ayuntamiento de São Paulo en el período 1989-1992. Fueron analizados documentos y medidas adoptadas por la Secretaría Municipal de Educación. Se concluyó que las prioridades de la aplicación de la propuesta del PT titulada escuela pública popular han sido sintetizadas en cuatro ejes centrales: Democratización de la Gestión; Nueva Calidad de Enseñanza; Movimiento de Alfabetización de Jóvenes y Adultos (MOVA) y Democratización del Acceso.
La política educacional del PT en el Ayuntamiento de São Paulo (1989-1992): formulación y institucionalización
The educational policy of PT in São Paulo City Hall (1989-1992): formulation and institutionalization
Keywords: Partido dos Trabalhadores; política educacional; prefeitura municipal de São Paulo; Worker´s Party; educational policy; municipal government of São Paulo